PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN DENGAN GENDER SEBAGAI VARIABEL MODERASI PADA KONSUMEN MIE GACOAN DI BANDAR LAMPUNG - Deandra Putri Zahra; MS, Mahrinasari (Nusantara Hasana Journal, 2025)
This study aims to determine the effect of service quality on customer satisfaction of Mie Gacoan in Bandar Lampung; determine the effect of product quality on customer satisfaction of Mie Gacoan in Bandar Lampung; analyze gender as a moderating variable group influencing the relationship between service quality and customer satisfaction of Mie Gacoan in Bandar Lampung; and analyze gender as a moderating variable group influencing the relationship between product quality and customer satisfaction of Mie Gacoan in Bandar Lampung. The service quality variable has a positive and significant effect on customer satisfaction of Mie Gacoan in Bandar Lampung. The highest rating was found on the indicator "Mie Gacoan employees are friendly to customers". This means that consumers feel that the friendly attitude of employees contributes greatly to comfort during their visit, thus increasing overall satisfaction. The customer satisfaction variable has a positive and significant effect on customer satisfaction of Mie Gacoan in Bandar Lampung. The highest rating was found on the indicator "Mie Gacoan products have a good taste". This means that consumers feel that the taste of food is the main factor in shaping customer satisfaction. The gender variable does not moderate the relationship between service quality and customer satisfaction of Mie Gacoan in Bandar Lampung. The results of the Multi-Group Analysis (MGA) showed no significant difference between the responses of male and female groups regarding customer satisfaction. This means that the service provided is consistent and received equally by both genders. Gender variables do not moderate the relationship between product quality and customer satisfaction at Mie Gacoan in Bandar Lampung. The results of the Multi-Group Analysis (MGA) showed no significant difference between the responses of male and female groups regarding customer satisfaction. This means that consumer perceptions of product quality are not influenced by gender.